:VENEWS How Art U? : Fare Mondi // Making Worlds artists_pavilions_events_maps. - Biënnale Venetië 2009 (Venetië : Venezia News, 2009)
Bayrle, Thomas ; Berti, Simone ; Bouchet, Mike ; Chan, Paul ; Yun, Chu ; Elagina, Elena ; Favaretto, Lara ; Finch, Spencer ; Friedman, Yona ; Gawde, Sunil ; et al.
Making Worlds, Venetië, 07.06 - 22.11.2009
kunstcatalogus